2018
DOI: 10.1136/tobaccocontrol-2017-054070
|View full text |Cite
|
Sign up to set email alerts
|

Dual use of electronic nicotine delivery systems (ENDS) and smoked tobacco: a qualitative analysis

Abstract: Dual use reflects both social and physical cues. It assisted participants to navigate smoking restrictions and allowed them to manage divergent norms. Policies that discourage smoking, particularly excise tax increases on smoked tobacco and smoke-free space restrictions, appear important in prompting ENDS use. Future research could explore whether these policies also help foster complete transition from smoking to exclusive ENDS use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 36 publications
2
56
0
1
Order By: Relevance
“…Recently published © 2019 Health Promotion Agency qualitative research indicates many smokers struggle with completely switching to e-cigarettes. 19 However, a recent populationbased online survey in the UK found that current dual users are more motivated to quit compared with individuals who previously used e-cigarettes. 20 The same study also found dual users to be less dependent on cigarettes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently published © 2019 Health Promotion Agency qualitative research indicates many smokers struggle with completely switching to e-cigarettes. 19 However, a recent populationbased online survey in the UK found that current dual users are more motivated to quit compared with individuals who previously used e-cigarettes. 20 The same study also found dual users to be less dependent on cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have found users' difficulties with the devices has hindered their cessation efforts. 19 Furthermore, while use of e-cigarettes alone is likely to be far less harmful than smoking combustible tobacco or dual use of combustible tobacco and e-cigarettes, it is still not risk-free and long-term harms are unclear. Consequently, follow-up advice on how to reduce e-cigarette consumption is also required in order to encourage the eventual cessation of e-cigarettes altogether.…”
Section: Implications For Public Healthmentioning
confidence: 99%
“…Half (50.6%) of current e-cigarette users were also current cigarette (conventional) smokers. Conventional smokers may concurrently use e-cigarettes, for example, to reduce or stop smoking, circumvent some smoke-free policies, or comply with social norms (37)(38)(39).…”
Section: Use Of Other Forms Of Tobaccomentioning
confidence: 99%
“…Many vapers have no plans to quit but rather use ECs to circumvent smoke-free policies or to maintain a similar habit as part of their daily routine. Thus, they do not t the strict inclusion criteria of RCTs as regards frequency of EC use, type of CC, dose or duration (15,25,57). Thus, the use of RCTs or the selection of subgroups with good prognostic outcomes does not re ect real-world use (26).…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, the few occasional smokers at t1 who persistently used ECs at t1 and t2 (n = 17) had signi cantly increased their smoking by 26 CC more per week than never-vapers. This could indicate that EC use may reinforce smoking-like behaviour (6,57), which could result in heavier CC use among occasional smokers. On the other hand, following the recommendations of Villanti et al (20), some but not all vapers with the best prognosis for our desired outcomes signi cantly reduced CC use by more than 20 cigarettes a week.…”
Section: Discussionmentioning
confidence: 99%